Hepatitis-C-virus-induced microRNAs dampen interferon-mediated antiviral signaling - Jarret, Abigail (Nat Med, 2016)
Hepatitis C virus (HCV) infects 200 million people globally, and 60–80% of cases persist as a chronic infection that will progress to cirrhosis and liver cancer in 2–10% of patients(1–3). We recently demonstrated that HCV induces aberrant expression of two host microRNAs (miRNAs), miR-208b and miR-499a-5p, encoded by myosin genes in infected hepatocytes(4). These miRNAs, along with AU-rich-element-mediated decay, suppress IFNL2 and IFNL3, members of the type III interferon (IFN) gene family, to support viral persistence. In this study, we show that miR-208b and miR-499a-5p also dampen type I IFN signaling in HCV-infected hepatocytes by directly down-regulating expression of the type I IFN receptor chain, IFNAR1. Inhibition of these miRNAs by using miRNA inhibitors during HCV infection increased expression of IFNAR1. Additionally, inhibition rescued the antiviral response to exogenous type I IFN, as measured by a marked increase in IFN-stimulated genes and a decrease in HCV load. Treatment of HCV-infected hepatocytes with type I IFN increased expression of myosins over HCV infection alone. Since these miRNAs can suppress type III IFN family members, these data collectively define a novel cross-regulation between type I and III IFNs during HCV infection.